2017
DOI: 10.31227/osf.io/as6g2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduction of Synthetic Fertilizer for Sustainable Agriculture: Influence of Organic and Nitrogen Fertilizer Combination on Growth and Yield of Green Mustard

Abstract: Abstract-On the other hand, application of both organic fertilizers at rate of 25 Mg ha -1 without addition nitrogen fertilizer as other treatments did not provide significant differences on most variables observed. This indicated that application of organic fertilizer is able to reduce synthetic nitrogen fertilizer for green mustard production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Other studies showed that organic farming was also superior in the content of total nitrogen, NH 4 + , soil pH, microbial carbon and particulate organic matter carbon [7], [8], [9], [10]. The addition of N fertilizer to organic fertilization, however, did not provide an effect of total soil nitrogen of Ultisol as reported by [11].…”
Section: Introductionmentioning
confidence: 80%
“…Other studies showed that organic farming was also superior in the content of total nitrogen, NH 4 + , soil pH, microbial carbon and particulate organic matter carbon [7], [8], [9], [10]. The addition of N fertilizer to organic fertilization, however, did not provide an effect of total soil nitrogen of Ultisol as reported by [11].…”
Section: Introductionmentioning
confidence: 80%